Infraestrutura e desempenho do ensino médio, em escolas públicas da capital paulista da rede estadual - Carnaval, Marilya Mariany (2020)
Intending to understand if the school infrastructure is related to the school's performance, this work seeks to identify the relationship between the distribution of the districts in which the schools are located, the school infrastructure and the school's performance, evaluated according to the average grade of portuguese and mathematics at SARESP. The research hypothesis is that schools with good infrastructure conditions are more likely to be among the teaching units that achieved the highest rates and to be located in the districts with the best economic and social conditions. The research perspective in relation to the definition of the adopted infrastructure covers the set of material and structural requirements of each school building that is intended for the of people access and pedagogical use.The data sources include: information about the school's infrastructure in the school questionnaires of Prova Brasil and the average grade of portuguese and mathematics of SARESP, from 2013 and 2015. The material remains available on the website of the national institute for educational research (INEP). In the analyzes, it was possible to identify that the items “science laboratory” and “computers for the exclusive use of the school administration” were the ones that received the highest score in all strata of districts. In addition, it was noticed that there is a higher inequality on the infraestructure conditions in schools which are situated in lower socioeconomic districts.Based on the analysis of multiple linear regression, it is performance, in 2013, and it explains 1,1%, in 2015. Although these values are not significant from a statistical point of view, it may get the attention because of the increase, from one year to the next, of the weight of infrastructure. As a theoretical reference, the perspective of studies developed by thinkers of the critical theory of society, among them, Herbert Marcuse, especially on the concept of technological rationality, Walter Benjamin, on the concept of experience, and Theodor Adorno, on the concept training